The GOD system to determine the natural vulnerability of groundwater in the municipality of Teutônia (RS) - Feldkircher, Tiago; Löbler, Carlos Alberto; Silva, José Luiz Silvério da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Nowadays, knowledge of groundwater resources is extremely important, since industrial, agricultural and mining activities are expanding constantly, impacting in several ways on the quality of groundwater. The Teutônia municipality that is located in the countryside of Rio Grande do Sul state southern Brazil, isn’t different. Thus this study aims to identify the natural vulnerability of the aquifer to contaminatinon, calculate the potentiometric surface and spatialize these results. Wells that are registered at Companhia de Pesquisas de Recursos Minerais in Groundwater Information System (SIAGAS/CPRM) for the Teutônia mu nicipality was be used. Using the GOD system, there were analyzed 40 tubulado wells. They penetrate Serra Geral Aquifer System/SASG and Guarani Aquifer System/GAS. Were generated the vulnerability map and the potentiometric surface map, and there was identified that most of the wells presented a low level of vulnerability and areas of low potentiometric level are also more vulnerable to contamination. As a preliminary study, the results are important to help in the ground water resources management, as well as to open new work alternatives linked to groundwater of the section ion. The results are also useful for master plans and land use at local scale.